Asymptomatic Takayasu Aortitis Complicated by Type B Dissection. Issue 22 (1st December 2015) - Barison, Andrea; Nugara, Cinzia; Barletta, Valentina; Todiere, Giancarlo; Montebello, Elena; Rossi, Serena; Terrizzi, Anna; Tavoni, Antonio; Aquaro, Giovanni Donato
Abstract : Supplemental Digital Content is available in the text.